Long-lasting bank relationships and growth of firms - Alessandro Gambini; Alberto Zazzaro (Center for Economic Studies and ifo Institute (CESifo), 2010)
A puzzling but consistent result in the empirical literature on banking is that firms with close bank ties do not grow faster than bank-independent firms. In this paper, we reconsider the link between relationship lending and firms' growth, distinguishing firms by size and 'health'. The idea is that the beneficial effects of relationship lending on information asymmetries can be compensated by other negative capture, risk and externality effects which make relational banks reluctant to support long-term growth projects of client firms, and that the strength of these compensating effects varies with firm size and health status. We explore the influence of long-lasting bank relationships on employment and asset growth of a large sample of Italian firms. The main finding is that relationship lending hampers the efforts of small firms to increase their size, while it mitigates the negative growth of troubled, medium-large enterprises.
Keywords: G21; G34; 330; relationship lending; capture effects; firms' growth; Unternehmenswachstum; Klein- und Mittelunternehmen; Kreditgeschäft; Hausbank; Lieferanten-Kunden-Beziehung; Unternehmensentwicklung; Italien